2016
DOI: 10.1111/1462-2920.13589
|View full text |Cite
|
Sign up to set email alerts
|

Formation of propionate and butyrate by the human colonic microbiota

Abstract: SummaryThe human gut microbiota ferments dietary nondigestible carbohydrates into short-chain fatty acids (SCFA). These microbial products are utilized by the host and propionate and butyrate in particular exert a range of health-promoting functions. Here an overview of the metabolic pathways utilized by gut microbes to produce these two SCFA from dietary carbohydrates and from amino acids resulting from protein breakdown is provided. This overview emphasizes the important role played by crossfeeding of interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

74
1,353
6
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,774 publications
(1,589 citation statements)
references
References 75 publications
74
1,353
6
13
Order By: Relevance
“…Importantly, this study revealed changes in the expression of genes involved in host-glycan catabolism and trophic interactions between the gut commensals. This interplay leads to the formation of butyrate at the mucosal layer that is proposed to be beneficial to the host (Koh et al 2016, Louis andFlint 2017). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Importantly, this study revealed changes in the expression of genes involved in host-glycan catabolism and trophic interactions between the gut commensals. This interplay leads to the formation of butyrate at the mucosal layer that is proposed to be beneficial to the host (Koh et al 2016, Louis andFlint 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Anaerostipes caccae crossfed on a part of the mucin sugars liberated by Akkermansia muciniphila for central metabolism. In addition, Anaerostipes caccae can incorporate Akkermansia muciniphila-derived acetate for butyrate production via butyryl-CoA: acetate CoAtransferase enzyme (Duncan et al 2004, Louis and Flint 2017.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations